2023
DOI: 10.3390/ijerph20065061
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Mental Health in Pediatric Patients Following COVID-19

Abstract: The global coronavirus pandemic has significantly impacted public health and has been a research subject since its emergence in 2019. The acute phase of the disease leads to pulmonary and non-pulmonary manifestations, which in some individuals may progress to long-lasting symptoms. In this article, we conducted a narrative review of the current literature to summarize current knowledge regarding long COVID syndrome in children, focusing on cognitive symptoms. The review included a search of three databases (Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Currently, it is still not possible to explain how severe COVID-19 and MIS-C occur, especially in children who have come into contact with people with COVID-19. Therefore, for high-risk children and adolescents who become positive for SARS-CoV-2 following contact with patients with COVID-19, appropriate multidisciplinary management measures for several months are required [ 32 , 64 , 65 , 66 ].…”
Section: Long Covid Impact On the Health Of Children And Adolescentsmentioning
confidence: 99%
“…Currently, it is still not possible to explain how severe COVID-19 and MIS-C occur, especially in children who have come into contact with people with COVID-19. Therefore, for high-risk children and adolescents who become positive for SARS-CoV-2 following contact with patients with COVID-19, appropriate multidisciplinary management measures for several months are required [ 32 , 64 , 65 , 66 ].…”
Section: Long Covid Impact On the Health Of Children And Adolescentsmentioning
confidence: 99%
“…In a case-control study of 25 children aged 12 to 17 years, significant impairment was found in memory, attention, visual gnosis, visual-spatial function, kinesthetic and dynamic praxis, and verbal and non-verbal components of thinking both 1–2 weeks after the acute phase and 2–12 months later [ 17 ]. A recent narrative review has reported that anxiety, sleep problems, and deficits in memory and concentration are the main long-term complaints in children after COVID-19 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The commonest include fatigue, breathing difficulties, headaches, myalgia or arthralgia, sleep disturbance, rhinorrhea, coughing, anosmia or dysgeusia, and sensory problems. 6 8 These symptoms can affect daily routine and school attendance. 9 This is particularly relevant for CYP as it can impact their education, development and wellbeing, health-related quality of life, and participation in social activities.…”
Section: Introductionmentioning
confidence: 99%
“…This understanding can support the development of strategies and treatments to reduce the impact on CYP 13 and the development of information for use in education, children’s support services, and health and social care. 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation